2016
DOI: 10.3208/jgssp.jpn-053
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal loading experiments on reinforced gravity type breakwater with steel walls

Abstract: In the 2011 off the Pacific coast of Tohoku Earthquake, especially coastal areas of the Pacific Ocean suffered extensive damage by tsunami. Then, there were needs to develop reinforcement methods for existing breakwaters against tsunami force. The authors proposed a method to reinforce a breakwater against tsunami with a steel wall behind the breakwater. This report presents the experimental results of the breakwater reinforcing method. In the proposed method, steel piles are inserted behind the breakwater and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…Recently, some efforts have been made to develop countermeasures for foundation of breakwater in order to make it resilient against damage caused by compound disaster triggered by earthquake and tsunami. Kikuchi et al [12] suggested a reinforced foundation using steel walls into foundation ground behind caisson. They developed the reinforced foundation to mitigate tsunami induced damage of breakwater.…”
Section: Countermeasures For Foundation Of Breakwatermentioning
confidence: 99%
“…Recently, some efforts have been made to develop countermeasures for foundation of breakwater in order to make it resilient against damage caused by compound disaster triggered by earthquake and tsunami. Kikuchi et al [12] suggested a reinforced foundation using steel walls into foundation ground behind caisson. They developed the reinforced foundation to mitigate tsunami induced damage of breakwater.…”
Section: Countermeasures For Foundation Of Breakwatermentioning
confidence: 99%
“…To improve the tsunami resistance of existing caisson-type composite breakwaters, a structure in which steel pipe piles are continuously driven behind the caisson and filled with soil between the caisson has been proposed [1,2]. Figure 1 shows a schematic of this structure.…”
Section: Introductionmentioning
confidence: 99%